KETERAMPILAN PROSES SAINS PADA PRAKTIKUM BIOKIMIA BERBASIS LINGKUNGAN - Dua Kuki, Agustina; Yohanita Nirmalasari, M.A. (Universitas Cokroaminoto Palopo, 2024)
This research aims to describe students' science process skills during the Biochemistry practicum. This research is a type of qualitative descriptive research that is applied to Chemistry Education students at Nusa Nipa University. Determination of the sample using purposive sampling technique. The data collection technique uses a science process skills observation sheet. The observation data was analyzed to obtain an average score for each aspect, then classified according to the categories very good, good, poor and very poor. Based on the research results, it shows that the science process skills in the aspect of categorizing and drawing conclusions obtained a score of 3-3.7, which is in the very good category.